Using linguistic-informed analysis to assess model texts for EFL reading and writing - Monaliza Hernandez Mamac; Lungguh Ariang Bangga (Indonesian Journal of Applied Linguistics, 2022)
English as Foreign Language (EFL) textbooks contain texts with topics integrated from content areas, such as science. In Thai basic education, learning in content areas is typically done in Thai. Therefore, EFL reading texts provide learners with primary exposure to building content knowledge in English. This raises an issue about how the language of these EFL texts is organised, and if they can help the learners’ transition to university where they are required to read content area texts in English. The paper provides an in-depth demonstration of how linguistic analysis can inform the choice of model texts for teaching EFL reading. It deploys a qualitative linguistic analysis method drawing on Systemic Functional Linguistics. The data are the scientific descriptive report texts in EFL textbooks used in a Southern Thailand secondary school. They are compiled in a small corpus, and one text is selected purposively to demonstrate how linguistic analysis can be used to assess the text. The text is analysed using a ‘top-down’ approach, from genre stratum down to the lexicogrammar, with the purpose of examining the text’s ideational, interpersonal, and textual resources to build up scientific knowledge. The findings show that the text does not conform to scientific descriptive reports’ discursive and linguistic features due to its extra stages, incomplete scientific taxonomies, relatively low technicality, low social distance and authority, and incoherent thematic flow. Hence, the quality of the text as a model becomes problematic. Learners learning from these teaching materials may experience challenges when they read authentic science texts at the university level. The paper offers a viable alternative methodological resource for educators to use a systematic, critical and linguistically-grounded evaluation in EFL reading classes.